Implementation in International Business Self‐regulation: The Importance of Sequences and their Linkages. (September 2015) - Porter, Tony; Ronit, Karsten
<x xml:space="preserve">Abstract</x> Self‐regulation by business is increasingly common internationally, but the effective implementation of international rules often continues to be seen as something that only states can carry out. We argue that more exclusively private forms of effective implementation can be constructed in self‐regulation. Drawing on research in private international law, public policy implementation and self‐regulation, we identify four distinct implementation sequences: monitoring, compliance, adjudication, and sanctioning. These sequences are sometimes constituted in response to deliberate integrated plans, but also come together in a decentralized manner. Many international business actors devise ways to carry out the sequences in order to implement rules that are important for them, reflecting a functional logic of implementation that is creative and pragmatic, and together constitute an important stage in the policy process of self‐regulation.